Diseminasi Analisis Risiko Operasional Di Area Produksi PT. XYZ Dengan Metode Enterprise Risk Management (ERM) - Indah Dwi Sefty; Akhmad Wasiur Rizqi; Hidayat Hidayat (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
In carrying out the production process, every company will definitely face risks. These risks can be in the form of risks that have small to large impacts. The risks that occur in the production area of ​​PT. XYZ, which is engaged in the production of packaged powder drinks, namely instant ground coffee, is the target for the dissemination of the study results. This activity aims to disseminate the impact that will occur from the risks and solutions that need to be done to deal with these risks with reference to the study literature. To identify risks, the literature uses an Enterprise Risk Management (ERM) approach. This method requires factual data obtained from interviews with the Head of the Production Division of PT. XYZ as a partner, and direct observations in the production area. The results of this dissemination activity indicate that the operational risks that may occur in the production area of ​​PT. XYZ broadly includes: human resource risk, machine breakdown risk, production area cleanliness risk, and powder processing delays. Related to company secrets, the company name and documentation of dissemination activities in the form of photos is not displayed.